Gums and Resins: Untapped potential of agroforestry systems for livelihood support - Prasad, Rajendra; Dhyani, S.K.; Tripathi, V. D.; Alam, B.; Ajit, Ajit; Handa, A. K.; Singh, Ramesh (Indian Farming, 2015)
Agroforestry offers options for different combinations of gum / resin yielding trees, crops and fruit trees for better utilization of available resources and increasing productivity on sustainable basis. Agrisiliviculture models can suitably be adopted wherein the density of the fruit crops and the trees are altered to provide returns throughout the year. These agroforestry models offer opportunities for increasing tree cover, enhancing productivity of gums, resins and fruits, and insurance to ecological stability.